2016
DOI: 10.1128/iai.01348-15
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Murine Peripheral Blood Lymphocytes Provide Immune Correlates That Predict Francisella tularensis Vaccine Efficacy

Abstract: We previously identified potential correlates of vaccine-induced protection against Francisella tularensis using murine splenocytes and further demonstrated that the relative levels of gene expression varied significantly between tissues. In contrast to splenocytes, peripheral blood leukocytes (PBLs) represent a means to bridge vaccine efficacy in animal models to that in humans. Here we take advantage of this easily accessible source of immune cells to investigate cell-mediated immune responses against tulare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 38 publications
(63 reference statements)
3
32
0
Order By: Relevance
“…tularensis is a facultative intracellular bacterium, cellular immune responses are thought to be of prime importance in protection. Indeed, experiments in mice have shown that T cell production of IFN-γ or control of bacterial replication in infected macrophages are associated with protection [ 24 , 25 ]. A recent paper has shown that cell-mediated immune responses can also be seen in human PBMC from LVS recipients bolstering the potential for measuring cellular immune responses in a clinical trial [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…tularensis is a facultative intracellular bacterium, cellular immune responses are thought to be of prime importance in protection. Indeed, experiments in mice have shown that T cell production of IFN-γ or control of bacterial replication in infected macrophages are associated with protection [ 24 , 25 ]. A recent paper has shown that cell-mediated immune responses can also be seen in human PBMC from LVS recipients bolstering the potential for measuring cellular immune responses in a clinical trial [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…protection (29)(30)(31)(32), but we recognized that inbred mouse models may be limited by lack of genetic diversity; we therefore initiated studies in DO mice in part to extend that work. Using the only currently licensed tuberculosis vaccine, we found that the DO population readily controlled systemic BCG bacterial burdens (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays utilizing coculture of F. tularensis infected BMDM and splenocytes from immunized mice were performed as previously described (35,38). Briefly, bone marrow was harvested from immunologically naive mice and cultured for 1 week in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% conditioned medium from the LADMAC cell line as a source of macrophage colony-stimulating factor (M-CSF), as well as 10% fetal bovine serum (FBS) (Atlanta Biologicals, Flowery Branch, GA), 200 mM L-glutamine (Gibco, Grand Island, NY), and 10 mM HEPES buffer (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that treatment of macrophages with IFN-␥ results in macrophage activation and killing of intracellular organisms (35,38). Therefore, in the same coculture system, the ability of the splenocytes to control intramacrophage replication of F. tularensis LVS was analyzed.…”
Section: Immunization Of Mice With Lvs-v Elicits Serummentioning
confidence: 99%
See 1 more Smart Citation